Preharvest application of beneficial fungi as a strategy to prevent postharvest mycotoxin contamination: A review. (August 2018) - Sarrocco, Sabrina; Vannacci, Giovanni
Abstract: The continuous pursuit of food quality, the need to feed an increasing global population and the legislative requirement to reduce the input of chemicals in the environment and in agriculture are seen as a very pressing "sword of Damocles", all highlighting the importance of the discovery and development of alternative strategies to guarantee food security. Beneficial fungi, both filamentous fungi and yeasts, are well-known as potential biocontrol agents for use in crop protection, as part of integrated or biological strategies, and represent one of the possible solutions to these needs. Among all the possible plant pathogens potentially affecting crops, mycotoxigenic fungi are considered as the main threat to food security, as they are present as contaminants in the main sources of nutrition for the population worldwide. Reducing mycotoxin contamination in produce during postharvest is one of the greatest challenges. The prevention of mycotoxigenic plant pathogens, mostly during preharvest, is considered as a valid strategy to reduce the risks associated with the mycotoxin contamination of processed food and feed. We present an overview of the possible applications of beneficial fungi in the preharvest of cereals, grapes and apples, in order to control the attack of these crops by important mycotoxigenic plant pathogens such as Fusarium, Aspergillus and Penicillium spp., respectively. We also examine the effects of these applications in terms of reduction of the risk of mycotoxin contamination such as trichothecenes ( Fusarium ), aflatoxins and ochratoxins ( Aspergillus ) and patulin ( Penicillium ), at a postharvest stage. Finally, the use of modern technologies, such as Next Generation Sequencing (NGS), is also discussed in terms of improving the success of beneficial fungi in preventing mycotoxin contamination. Highlights: The use of preharvest beneficial fungi against postharvest toxigenic ones is reported. The risk of mycotoxin accumulation in different plant/pathogen systems is discussed. NGS as a tool to reply to the increasing demand for food security are discussed. A hypothetically ideal pathway for the management of plant diseases is proposed.